Sul valore “induttivo” del razionalismo di Gaston Bachelard - Abramo, Maria Rita (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2023)
The purpose of this paper is to reflect on the nature of Bachelard’s rationalism. Among his early writings, The Inductive Value of Relativity (1929) reveals all the epistemological value of the fundamental notion of induction. Beyond the historical-critical value of Bachelard’s interpretation of Relativity, in the inductive impetus of thought that makes science, we can recognize some traces of the specific rationalist tonus that underpins the later philosophy of ‘re’ (‘to restart’, ‘to renew’, ‘to reorganize’). Precisely the anomalous manner of Bachelard’s use of the concept of induction would, in our opinion, perhaps unpredictably, have supported Bachelard’s hermeneutic rationalist perspective on the relationship between the real and the virtual and on the meaning of the concepts of experience and scientific reason, within a cultural climate that had not yet finished coming to terms with Descartes. Finally, hints of a certain vocation for complex thought emerge, inviting us to glimpse unexplored facets of Gaston Bachelard’s philosophy.